Wandering Greeks : the ancient Greek diaspora from the age of Homer to the death of Alexander the Great - Garland, Robert (Princeton University Press, 2017)
Most classical authors and modern historians depict the ancient Greek world as essentially stable and even static, once the so-called colonization movement came to an end. But this work argues that the Greeks were highly mobile, that their movement was essential to the survival, success, and sheer sustainability of their society, and that this wandering became a defining characteristic of their culture. Addressing a neglected but essential subject, this text focuses on the diaspora of tens of thousands of people between about 700 and 325 BCE, demonstrating the degree to which Greeks were liable to be forced to leave their homes due to political upheaval, oppression, poverty, warfare, or simply a desire to better themselves